The Livebirth Rate Per In Vitro Fertilization Cycle Is Higher Than The Cumulative Live Birth Rates of Intrauterine Insemination for Patients of Poseidon Group 3 With Unexplained Infertility - Yixuan Wu; Haiying Liu; Jianqiao Liu (Frontiers in Endocrinology, 2021)
BackgroundNo studies have been done to examine the efficacy of IVF and intrauterine insemination (IUI) for the treatment of young patients with unexplained infertility and low ovarian reserve, although it is becoming an increasingly significant indication for in-vitro fertilization (IVF). The goal of this research was to compare the efficacy of IVF with IUI on Poseidon group 3 patients with unexplained infertility (PG3&UI).MethodsThis was a retrospective analysis of PG3&UI patients who had IVF/intracytoplasmic sperm injection (ICSI) or IUI at the Third Affiliated Hospital of Guangzhou Medical University between January 1, 2015, and March 31, 2021. To equalize the baseline characteristics of the IVF/ICSI and IUI groups, propensity score matching (PSM) was utilized. Intention-to-treat (ITT) and per-protocol (PP) analyses were used to compare the differences in live births. To discover variations in time to biochemical pregnancy leading to live birth, Kaplan-Meier curves were produced. To evaluate the expenses per live birth between two procedures, a cost-effective analysis was done.ResultsAccording to ITT analysis, the live birth rate for the IVF/ICSI group was substantially higher than the cumulative live birth rate (CLBR) for the IUI group (22.6% (38/168) vs. 11.3% (19/168), RR 2.00, 95% CI 1.20-3.32, P = 0.006). In the PP analysis, the live birth rate was 23.0% (38/165) in the IVF/ICSI group and 11.7% (19/162) in the IUI group (RR = 1.96, 95% CI 1.18-3.26, P = 0.007). When censored at 365 days, the Kaplan-Meier analysis revealed that the IVF/ICSI group had a higher live birth rate than the IUI group (log-rank test χ²= 6.025; P = 0.014). However, when the two groups were censored at 180 days, the live birth rates were not substantially different (log-rank test χ²= 3.847; P = 0.05). The number of hospital visits per live birth in the IUI group was higher than in the IVF/ICSI group (85 vs. 48). The overall cost of a live birth was comparable across the two groups (¥132242 vs. ¥131611), while the medical expenses for a live delivery from IVF/ICSI were higher than those from IUI (¥118955 vs. ¥108279).ConclusionsThe livebirth rate per IVF/ICSI cycle with at most one embryo transfer is higher than the CLBR of IUI, with fewer hospital visits and similar expenses.